E-Learning training for physical education teachers: The experience of veneto SSIS - Carraro, A.; Bertollo, M. (International Journal of Computer Science in Sport, 2002)
After a long period of stasis, in the last years a general renewal process in every level of the educational institutions, from primary school to university, has begun in Italy. Many universities are currently engaged in planning and realizing specific postgraduate courses for the initial preparation of teachers. Veneto SSIS (School of Specialization for Secondary School Teachers) trains teachers for different subjects using two types of courses: traditional in-presence courses and on-line courses in a blended modality. In this paper we present a comparative study of these two teaching/learning methodologies. As regards teaching inpresence, the on-line preparation allows an uninterrupted virtual contact between students and professors and among students by means of e-forum and mailing lists. Through on-line training, students can experiment constructive modality of cooperative learning that could be more effective with respect to other traditional learning methodology.